The Meaning Of Love In Poetry “ al-Ḥubb Alays“ By Jalaludin Rumi: Ma'na al-Hubb Fī Shaw‘īr "al-Ḥubb Alays" Karāyah Jalāluddīn Rūmī - Abdul Basith, Muhammad Syafi'i; Wahyudi, Jarot (An-Nahdah Al-'Arabiyah, 2025)
This research aims to find the meaning of love contained in the poem ‘Alaisal Hubb’ by Jalaludin Rumi with a semantic approach. The method used in this research is descriptive qualitative method with the basis of the main document, namely the poem Alaisal Hubb. The data of this research is qualitative data in the form of facts, information, stanzas and images obtained by researchers from research sources, namely the poem Alaisal Hubb by Jalaludin Rumi. The data collection technique uses semantic and pragmatic approaches, namely by analysing how meaning is influenced by communicative context, including implicature or hidden meaning, and pragmatics in a research object, so as to obtain a complete concept to understand the meaning of love in depth in the object of research. The result of this study is that the meaning of love which has only been interpreted as a universal expression of feelings, but after a deeper study of love in the poem is not only the meaning of love between humans but the meaning of love itself is a union with God or a spiritual lover who transcends physical and material boundaries. As well as to reach a higher spiritual dimension and connect humans with their creator. With the use of implied language by the narrator, it also creates a deep meaning or message that the narrator wants to convey through literary works.   يهدف هذا البحث إلى الكشف عن معنى الحب الكامن في قصيدة أليس الحب لجلال الدين الرومي من خلال المنهج الدلالي. والمنهج المتَّبع في هذا البحث هو المنهج الوصفي النوعي، بالاعتماد على الوثيقة الأساسية وهي قصيدة أليس الحب. أما بيانات هذا البحث فهي بيانات نوعية تتمثل في الحقائق والمعلومات والأبيات والصور التي حصل عليها الباحث من مصادر البحث، وهي قصيدة أليس الحب لجلال الدين الرومي. وتتم عملية جمع البيانات باستخدام المنهج الدلالي والبراغماتي، وذلك من خلال تحليل كيفية تأثر المعنى بالسياق الاتصالي، بما في ذلك التضمين أو المعنى الخفي، والجوانب البراغماتية في موضوع البحث، حتى يتم التوصل إلى مفهوم متكامل لفهم معنى الحب بعمق في موضوع البحث. وتوصلت نتائج البحث إلى أن معنى الحب الذي كان يُفهم في السابق على أنه مجرد تعبير عن شعور إنساني عالمي، بعد الدراسة المتعمقة في القصيدة، تبيَّن أنه لا يقتصر على الحب بين البشر، بل إن معنى الحب ذاته هو الاتحاد بالله أو المحبوب الروحي الذي يتجاوز الحدود الجسدية والمادية. كما أن هذا الحب يهدف إلى الوصول إلى بُعد روحي أسمى وربط الإنسان بخالقه. واستخدام الشاعر للغة الموحية أضفى أيضًا معنى ورسالة عميقة أراد إيصالها من خلال العمل الأدبي.   Penelitian ini bertujuan untuk menemukan makna cinta yang terkandung dalam puisi Alaisal Hubb karya Jalaludin Rumi dengan pendekatan semantik. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan dasar dokumen utama, yaitu puisi Alaisal Hubb. Data penelitian ini berupa data kualitatif dalam bentuk fakta, informasi, bait, dan citra yang diperoleh peneliti dari sumber penelitian, yaitu puisi Alaisal Hubb karya Jalaludin Rumi. Teknik pengumpulan data menggunakan pendekatan semantik dan pragmatik, yaitu dengan menganalisis bagaimana makna dipengaruhi oleh konteks komunikatif, termasuk implikatur atau makna tersembunyi, serta aspek pragmatik pada objek penelitian, sehingga diperoleh konsep yang utuh untuk memahami makna cinta secara mendalam pada objek penelitian. Hasil penelitian ini menunjukkan bahwa makna cinta yang selama ini hanya dipahami sebagai ungkapan perasaan universal, setelah dikaji lebih dalam melalui puisi ini, ternyata tidak hanya dimaknai sebagai cinta antarmanusia, tetapi cinta itu sendiri merupakan penyatuan dengan Tuhan atau kekasih spiritual yang melampaui batas fisik dan materi. Cinta tersebut mengantarkan manusia pada dimensi spiritual yang lebih tinggi dan menghubungkan manusia dengan Sang Pencipta. Penggunaan bahasa tersirat oleh penyair juga menciptakan makna atau pesan mendalam yang ingin disampaikan melalui karya sastra.